PENGARUH MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN MENGINGAT GERAKAN PADA PENARI DI SANGGAR TARI DHARMA PRAGINA DEWI - Dewi, Putu Muslika; Dewi, Putu Muslika; Arisandy, Desy (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2018)
This study aimed to explore the influence of audiovisual media to memory in dancer at dance studio dharma pragina dewi. Hyphothesis in there are influence of audiovisual media to memory in dancer at dance studio dharma pragina dewi. This research use observation checklist the ability remember to movement of galang bulan dance. This research use experiment methods. The sample of this study were dancer of studio dance dharma pragina dewi which numbered 20 people with data analisys independent sample t-test techniques. The results of computer analysis of research data using SPSS 20.0 for windows, obtained value the results of independent sample t-test t = -7.415 and p = 0,000 (p <0.05). this suggest that the hyphotesis is accepted.  The result of this analysis can be stated that there is the effect of audiovisual media is significant to memory in dancer at dance studio dharma pragina dewi.